A lithium-ion battery silicon-carbon negative electrode material and its application
By adopting a silicon-carbon negative electrode material with a double-layer coated core-shell structure, using the porous silicon-oxygen compound buffer layer and the carbon shell layer, the repeated generation of solid electrolyte interface films caused by volume expansion and contraction in lithium-ion batteries is solved. With the problem of rupture, high cycle stability and long life battery performance is achieved.
Patent Information
- Application Number
- CN202211509406.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-29
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-11-29
AI Technical Summary
The volume expansion and contraction of the silicon-based materials of lithium-ion batteries during the embedding and deliquification process leads to repeated generation and rupture of the solid electrolyte interface film, consuming the limited electrolyte inside the battery, affecting the electron conduction path and charge and discharge effect of the silicon.
The silicon-carbon negative electrode material adopts a double-layer coated core-shell structure. The inner layer is a silicon core, the middle is a porous silicon oxide buffer layer, and the outer layer is a carbon shell. Silica is converted into porous silicon oxide through high temperature thermal reduction to form a complete aerogel-covered structure, reducing structural damage caused by volume effects and improving the cyclic stability of the material.
Effectively reduces structural damage caused by volume expansion of silicon powder, reduces the repeated generation and rupture of solid electrolyte interface mask, improves the cycle stability and service life of the battery, has the first-effect retention rate of more than 85%, and charges and discharges for 50 cycles. The rear capacity retention rate is as high as more than 90%.
Smart Images

Figure CN115663160B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrode materials, and in particular to a lithium-ion battery silicon-carbon negative electrode material and application thereof. Background Art
[0002] Lithium-ion battery is a secondary battery that mainly relies on the movement of lithium ions between the positive and negative electrodes to work. + It embeds and de-embeds back and forth between the two electrodes. It has the advantages of high voltage, high specific energy, long cycle period, and low environmental pollution, and has become the first choice for secondary energy. It is widely used in mobile phones, laptops, portable power tools, and electric vehicles. As the application scenarios of lithium-ion batteries become more and more extensive, higher requirements are also placed on the performance of lithium-ion batteries. It is a general trend to develop lithium-ion battery materials with higher specific capacity and better cycle performance.
[0003] Silicon-based materials have high theoretical lithium storage capacity (4200mAh / g) and low lithium desorption voltage platform (0.5V), and are one of the most promising new lithium-ion battery negative electrode materials. However, the volume expansion and contraction of silicon materials during the lithium insertion and desorption process is as high as 300%-400%, and there are serious interface side reactions, which hinder their practical application. Among them, high internal stress will cause the pulverization of silicon particles, and continuous expansion and contraction will cause the contact between active materials and conductive agents and binders to deteriorate, thereby affecting conductivity; and the pulverization of particles and continuous expansion and contraction will cause repeated generation and rupture of the solid electrolyte interface film (SEI), consuming the limited electrolyte inside the battery, thereby affecting the electronic conduction path of silicon.
[0004] CN201711015729.6 discloses a titanium silicon carbon negative electrode material with a core-shell pomegranate structure and a preparation method thereof, wherein the titanium silicon carbon negative electrode material is composed of a core composed of Si / SiO2 secondary powder, a carbon element material shell coated on the surface of the Si / SiO2 secondary powder, and a titanium element material shell composed of a titanium source material coated on the surface of the carbon element material shell. The titanium silicon carbon negative electrode material is prepared by carbon coating the Si / SiO2 secondary powder and then coating the obtained C / Si / SiO2 tertiary particles with titanium. This technical solution can solve the problem of repeated generation and rupture of the solid electrolyte interface film caused by the volume expansion and contraction of silicon materials to a certain extent. However, the silicone gel is dissociated on the surface of the silicon powder by the dissociator, and actually forms a silicone gel semi-coated silicon powder structure. A considerable part of the silicone gel is embedded in the silicon powder, and the silicone gel coating effect on the silicon powder cannot be guaranteed. The volume expansion and contraction of the silicon powder is likely to cause the carbon layer and titanium layer of the outer shell to rupture, thereby causing repeated generation and rupture of the solid electrolyte interface film, consuming the electrolyte and affecting the charge and discharge effect. In addition, the poor conductivity of silicon dioxide can easily lead to an increase in internal resistance, while adding a titanium material outer shell will be too costly, which is not conducive to practical application. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a silicon-carbon negative electrode material for lithium-ion batteries to solve the problem that the existing silicon-based materials expand and contract in volume, resulting in repeated generation and rupture of the solid electrolyte interface film, consuming the limited electrolyte inside the battery, thereby affecting the electronic conduction path of silicon and affecting the charging and discharging effect.
[0006] Further provided are a preparation method of the lithium-ion battery silicon-carbon negative electrode material and an application thereof.
[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0008] A lithium-ion battery silicon-carbon negative electrode material has a double-layer coated core-shell structure, which comprises a silicon core, a buffer layer and a carbon layer from the inside to the outside; the mass fraction of each layer is: 40-60% for the silicon core, 35-55% for the buffer layer, and 5-10% for the carbon shell.
[0009] Furthermore, the buffer layer is a porous silicon-oxygen compound SiOx, wherein 0<x<2.
[0010] Further, the following preparation method is adopted to obtain:
[0011] S1. Preparation of SiO2 aerogel-coated silicon powder structure Si@SiO 2 ;
[0012] S2, silicon dioxide aerogel coated silicon powder structure Si@SiO 2High temperature thermal reduction is performed to obtain a porous silicon oxide compound-coated silicon powder structure Si@SiOx, wherein 0<x<2;
[0013] S3, adding carbon material to the porous silicon oxide compound coated silicon powder structure Si@SiOx obtained in step S2 to coat the carbon material to obtain a silicon-carbon negative electrode material Si@SiOx@C;
[0014] Further, the step S1 comprises:
[0015] S11, dissolving methyl silicate and monomethyltrimethoxysilane in methanol, adding 0.15M hydrochloric acid, placing in a 40-60°C water bath with magnetic stirring, and hydrolyzing for 1-5 hours; adding methanol again to obtain silica sol; wherein the molar ratio of the methyl silicate, monomethyltrimethoxysilane, methanol, and hydrogen chloride is 1:0.1-2:5-15:0.01-1; the molar ratio of the methyl silicate to the methanol added again is 1:21-26;
[0016] S12, adding silicon powder to the silicon dioxide sol obtained in step S11, and continuously stirring to obtain a sol in which the silicon powder is evenly dispersed; wherein the mass volume ratio of the silicon powder to the silicon dioxide sol is 24.5-56 g:380-440 mL;
[0017] S13, adding an alkaline alcohol solution to the sol in which the silicon powder is uniformly dispersed obtained in step S12, controlling the gelation time to be 1-10 min, obtaining a wet gel, and then placing it in a supercritical carbon dioxide environment for displacement drying for 1-20 h; grinding and sieving the dried material to obtain a silicon dioxide aerogel-coated silicon powder structure Si@SiO 2 .
[0018] Furthermore, step S2 comprises: placing the silica aerogel-coated silicon powder structure Si@SiO2 obtained in step S1 in a hydrogen and argon mixed atmosphere at 1100-1400°C for high temperature treatment for 1-5 hours to obtain a porous silicon oxide compound-coated silicon powder structure Si@SiOx (0<x<2); wherein the volume fraction of hydrogen in the mixed gas is 5%-20%.
[0019] Further, the step S3 comprises:
[0020] S31, the porous silicon-oxygen compound-coated silicon powder structure Si@SiOx (0<x<2) obtained in S2 and the carbon source are mixed in a solution with a mass ratio of 1:1 of ethanol and water at a mass ratio of 1:1, and ultrasonicated for 30-100 minutes;
[0021] S32, placing the mixed solution after ultrasonic treatment in a hydrothermal reactor, and hydrothermally treating it in an environment of 100-300° C. for 1-10 h;
[0022] S33, after being completely dried in a blast oven, carbonize at 300-600°C for 30-360 min to obtain the silicon-carbon negative electrode material Si@SiOx@C.
[0023] Furthermore, the silicon powder has a particle size of 200-1000 nm.
[0024] An application of silicon-carbon negative electrode material for lithium-ion batteries, wherein the silicon-carbon negative electrode material prepared by the above method is used to prepare negative electrode plates. The negative electrode plates can be used for batteries of various types, including button batteries and cylindrical batteries.
[0025] Furthermore, the preparation method of the electrode negative electrode sheet is as follows: according to the mass percentage, 60-80% of the silicon-carbon negative electrode material and 2-25% of the conductive agent are fully ground, and then 5-20% of the binder is added, mixed thoroughly, and coated on the copper foil with a thickness of 200 μm, air-dried until the surface is completely solidified, and compacted and dried in a vacuum environment at 120°C for 5-20 hours to obtain the electrode negative electrode sheet.
[0026] Furthermore, in terms of mass percentage, the silicon-carbon negative electrode material is 70%, the conductive agent is 20%, and the binder is 10%, or the silicon-carbon negative electrode material is 80%, the conductive agent is 10%, and the binder is 10%.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] 1. The silicon-carbon negative electrode material for lithium-ion batteries of the present invention is a double-layer coated core-shell structure, and a silicon oxide compound aerogel buffer layer is used between the silicon core and the carbon shell. Since the aerogel is a porous material with a large specific surface area, there is a part of the gap between the silicon powder and the aerogel after the silicon powder is coated, and the aerogel has a certain flexibility. After being squeezed, the gap and its flexibility can provide a part of the space required for expansion, reducing the structural damage caused by the volume effect. In addition, the aerogel layer of the present invention is completely coated on the surface of the silicon powder, allowing the silicon particles to expand freely without destroying the outer carbon shell, thereby ensuring that the SEI film on the shell surface will not be destroyed.
[0029] 2. The main component of the material of the buffer layer of the present invention is silicon oxide, and the expansion rate is effectively reduced, thereby improving the overall cyclic stability of the material. The uniform carbon shell can prevent the electrolyte from reaching the nano-silicon surface in the shell, thereby preventing the occurrence of interface side reactions, while the ions can diffuse to the silicon core through the carbon shell, and the silicon undergoes lithiation. Even if there are some small defects or pinholes on the slightly damaged carbon shell, the SEI film formed on the carbon shell will fill the holes through circulation, isolating the shell from the electrolyte. The carbon shell layer has both electronic conductivity and ionic conductivity, which makes good kinetic performance possible.
[0030] 3. The silicon-carbon negative electrode material for lithium-ion batteries of the present invention adopts the method of fully encapsulating silicon powder with aerogel to reserve space for the expansion of silicon-based materials and reduce the structural damage caused by the volume effect; and adopts high-temperature thermal reduction to convert silicon dioxide into porous silicon oxide to improve the overall cycle stability of the material; at the same time, the oxygen content in the material is reduced, and the side reactions such as the generation of lithium silicate by the negative electrode of the battery during the charging and discharging process are reduced, the loss of lithium ions is reduced, and the service life of the battery is increased. The electrode material prepared by the preparation method of the present invention has high first efficiency and high cycle life; the first efficiency is above 85%, and the capacity retention rate after 50 cycles of charging and discharging is as high as above 90%. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 A schematic diagram of the microstructure of the silicon-carbon negative electrode material for a lithium-ion battery of the present invention;
[0032] In the figure, 1-silicon core; 2-porous silicon oxide buffer layer; 3-carbon shell. DETAILED DESCRIPTION
[0033] The present invention will be further described below in conjunction with the embodiments.
[0034] See also Figure 1 The present invention discloses a lithium-ion battery silicon-carbon negative electrode material, which is a double-layer coated core-shell structure, which comprises a nano-scale silicon core 1, a porous silicon oxide buffer layer 2 and a carbon shell 3 from the inside to the outside.
[0035] The mass fractions of each layer are as follows: silicon core 40-60%, porous silicon oxide buffer layer 35-55%, and carbon shell 5-10%.
[0036] The buffer layer is a porous silicon oxide compound SiOx layer; wherein 0<x<2.
[0037] The lithium-ion battery silicon-carbon negative electrode material of the present invention has a buffer layer designed between the silicon core and the carbon shell. The buffer layer is a silicon oxide compound aerogel layer. Since the aerogel is a porous material with a large specific surface area, there is a part of gap between the silicon powder and the aerogel after the silicon powder is coated, and the aerogel has a certain flexibility. After being squeezed, the gap and its flexibility can provide a part of the space required for expansion, thereby reducing the structural damage caused by the volume effect; and the aerogel layer of the present invention is completely coated on the surface of the silicon powder, allowing the silicon particles to expand freely without destroying the outer carbon shell, thereby ensuring that the SEI film on the shell surface will not be destroyed.
[0038] The main component of the buffer layer material is silicon oxide, which effectively reduces the expansion rate and improves the overall cycle stability of the material. The uniform carbon shell can prevent the electrolyte from reaching the nano-silicon surface inside the shell, preventing the occurrence of interface side reactions, while ions can diffuse to the silicon core through the carbon shell, and silicon undergoes lithiumization. Even if there are some small defects or pinholes on the slightly damaged carbon shell, the SEI film formed on the carbon shell will fill the holes through the cycle, isolating the shell from the electrolyte. The carbon shell has both electronic and ionic conductivity, which makes good kinetic performance possible.
[0039] Example 1
[0040] A lithium-ion battery silicon-carbon negative electrode plate, the preparation method of which comprises the following steps:
[0041] S1. Dissolve 105g of methyl silicate and 75.5g of monomethyltrimethoxysilane in 333g of methanol, add 69g of 0.15M HCl solution, place in a 55°C water bath with magnetic stirring, and hydrolyze for 2h; after hydrolysis, add 465g of methanol and stir to obtain silica sol. Take 380mL of silica sol, add 24.5g of silicon powder with a particle size of 500nm, continue stirring, and obtain a sol with uniformly dispersed silicon powder;
[0042] During the hydrolysis process, monomethyltrimethoxysilane is used as a modifier, which can play a hydrophobic role, and the drying effect is better when drying the gel. Methanol is used as a solvent. The methanol solvent is added in two steps during the preparation of the sol, which can further enhance the hydrophobic effect of monomethyltrimethoxysilane and make the drying effect better. The role of hydrochloric acid is to adjust the pH and keep the reaction system under acidic conditions, making the system more stable.
[0043] S2, add 1.5M NH 3 ·H 2 O and 0.2 M NH 4 6.3 g of mixed alcohol solution of F, promoted gelation, gelation time 3′26″;
[0044] S3, the obtained gel was placed in a supercritical carbon dioxide (16Mpa, 40°C) environment, replaced and dried for 4h, ball-milled for 30min, and sieved to obtain a silica aerogel-coated silicon powder structure Si@SiO 2 ;
[0045] S4, take 10g of silica aerogel coated silicon powder structure Si@SiO 2 After being placed in a hydrogen-argon mixed atmosphere at 1300°C for high-temperature reduction for 30 minutes, the mixture was ball-milled for 1 hour and sieved to obtain a porous silicon-oxygen compound-coated silicon powder structure Si@SiOx (0<x<2);
[0046] S5. Take 2g of silicon oxide compound-coated silicon powder structure and 0.5g of glucose, mix them in a 1:1 mixture of ethanol and water, sonicate for 30min, then place the sonicated mixed solution in a hydrothermal reactor, hydrothermally treat at 100-300℃ for 60min, then place it in a blast oven to dry the water, and then heat it in N 2 In the atmosphere, carbonization was carried out at 400 ° C for 1 h to obtain the silicon-carbon negative electrode active material Si@SiOx@gluC. Among them, hydrothermal treatment can make the carbon crystal form better and achieve better coating effect.
[0047] Through SEM and AC-TEM detection, the silicon-carbon negative electrode active material has the following characteristics: Figure 1 The microstructure shown.
[0048] S6, take 0.7g of silicon-carbon negative electrode active material, 0.2g of acetylene black, and 6.7g of LA136D with a mass fraction of 1.5%, and apply them on the copper foil with a thickness of 200μm. Air dry until the surface is completely solidified, compact it, dry it in a vacuum environment at 120℃ for 8h, and cut it to make a cr2032 button half-battery.
[0049] Example 2
[0050] A lithium-ion battery silicon-carbon negative electrode plate, the preparation method of which comprises the following steps:
[0051] S1. Dissolve 56.25g of methyl silicate and 51g of monomethyltrimethoxysilane in 142g of methanol, add 33.5g of 0.15M HCl solution, place in a 55°C water bath with magnetic stirring, and hydrolyze for 2h; after hydrolysis, add 127.6g of methanol and stir to obtain silica sol. Take 430mL of silica sol, add 36.5g of silicon powder with a particle size of 500nm, continue stirring, and obtain a sol with uniformly dispersed silicon powder;
[0052] S2, adding 25.8 mL of 0.7 M NaOH alcohol solution to the sol in which the silicon powder is evenly dispersed to promote gelation, with a gelation time of 2′50″;
[0053] S3, the obtained gel was placed in a supercritical carbon dioxide (16Mpa, 40°C) environment, replaced and dried for 4h, ball-milled for 30min, and sieved to obtain a silica aerogel-coated silicon powder structure Si@SiO 2 ;
[0054] S4, take 40g of silica aerogel coated silicon powder structure Si@SiO 2 After being placed in a hydrogen-argon mixed atmosphere at 1300°C for high-temperature reduction for 60 minutes, the mixture was ball-milled for 1 hour and sieved to obtain a porous silicon-oxygen compound-coated silicon powder structure Si@SiOx (0<x<2);
[0055] S5. Take 5g of porous silicon oxide compound-coated silicon powder structure and 1g of glucose, mix them in a 1:1 mixture of ethanol and water, sonicate for 30min, then place the sonicated mixed solution in a hydrothermal reactor, hydrothermally treat at 100-300℃ for 30min, then place it in a blast oven to dry the water, and then place it in N 2 In the atmosphere, carbonization was carried out at 400 °C for 1 h to obtain the silicon-carbon negative electrode active material Si@SiOx@gluC.
[0056] Through SEM and AC-TEM detection, the silicon-carbon negative electrode active material has the following characteristics: Figure 1 The microstructure shown.
[0057] S6, take 0.7g silicon-carbon negative electrode active material, 0.2g acetylene black, 6.7g LA136D with a mass fraction of 1.5%, and apply it on the copper foil with a thickness of 200μm. Air dry until the surface is completely solidified, compact it, dry it in a vacuum environment at 120℃ for 10h, and cut it into cr2032 button half-cells.
[0058] Example 3
[0059] A lithium-ion battery silicon-carbon negative electrode plate, the preparation method of which comprises the following steps:
[0060] S1. Dissolve 56.3g of methyl silicate and 51g of monomethyltrimethoxysilane in 141.75g of methanol, add 33.5g of 0.15M HCl solution, place in a 55°C water bath with magnetic stirring, and hydrolyze for 2h; after hydrolysis, add 139g of methanol and stir to obtain silica sol. Take 440mL of silica sol, add 56g of silicon powder with a particle size of 500nm, continue stirring, and obtain a sol with uniformly dispersed silicon powder;
[0061] S2, adding 26.4 mL of 0.7 M NaOH solution to the sol in which the silicon powder is evenly dispersed to promote gelation, the gelation time is 3′5″;
[0062] S3, the obtained gel was placed in a supercritical carbon dioxide (16Mpa, 40°C) environment, replaced and dried for 4h, ball-milled for 30min, and sieved to obtain a silica aerogel-coated silicon powder structure Si@SiO 2 ;
[0063] S4, take 20g of silica aerogel coated silicon powder structure Si@SiO 2 After being placed in a hydrogen-argon mixed atmosphere at 1300°C for high-temperature reduction for 60 minutes, the mixture was ball-milled for 1 hour and sieved to obtain a silicon oxide compound-coated silicon powder structure Si@SiOx (0<x<2);
[0064] S5. Take 5g of silicon oxide compound-coated silicon powder structure and 1g of glucose, mix them in a 1:1 mixture of ethanol and water, sonicate for 30min, then place the sonicated mixed solution in a hydrothermal reactor, hydrothermally treat at 100-300℃ for 30min, then place it in a blast oven to dry the water, and then heat it in N 2 In the atmosphere, carbonization was carried out at 400 °C for 1 h to obtain the silicon-carbon negative electrode active material Si@SiOx@gluC.
[0065] Through SEM and AC-TEM detection, the silicon-carbon negative electrode active material has the following characteristics: Figure 1 The microstructure shown.
[0066] S6. Take 0.8g of silicon-carbon negative electrode active material, 0.1g of acetylene black, and 2g of LA133 with a mass fraction of 5%, and apply them on the copper foil with a thickness of 200μm. Air-dry until the surface is completely solidified, compact it, dry it in a vacuum environment at 120℃ for 8h, and cut it to make a cr2032 button half-battery.
[0067] In specific implementation, methyl silicate can be replaced by other silicate reagents such as ethyl silicate (TEOS), methanol can be replaced by ethanol (ETOH), and monomethyltrimethoxysilane can be replaced by methylethoxysilane reagents, and the molar ratio remains unchanged.
[0068] The carbon source can be one or more of glucose, sucrose, starch, citric acid, polyvinyl pyrrolidone, and polydopamine.
[0069] The conductive agent may be acetylene black, Ketjen black or carbon nanotubes; the binder may be one or more of LA133, LA136D, CMC and SBR.
[0070] Comparative Example 1: Coating SiO on nano-silicon (100-300nm) particles 2 The sacrificial layer (made by sol-gel method) is then coated with a polydopamine layer, which is carbonized to form a nitrogen-doped carbon coating. The SiO2 is selectively removed by hydrofluoric acid (HF) treatment. 2 After the sacrificial layer, the yolk-shell Si@void@C structure is obtained. This method uses HF, which is dangerous and polluting, and has high cost and difficulty in preparation.
[0071] Comparative Example 2: Silicon (silicon powder with an average particle size of 120 nm), asphalt powder and graphite in a mass ratio of 2:1:1 were used to heat at 900°C for 1 hour in a nitrogen atmosphere and mechanically synthesize a nano-silicon / carbon composite material using a high-energy grinder (1 hour). This solution has high requirements on the quality of silicon powder, and the performance of the obtained product is poor.
[0072] Comparative Example 3: Silicon (silicon powder average particle size 50nm) and asphalt powder with a mass ratio of 5:95 were used to perform high-energy mechanical grinding (1h) in a nitrogen atmosphere to obtain a silicon-carbon composite material. This method has a small silicon powder particle size, high cost, and average performance.
[0073] The performance indicators of the half-cells of the embodiments of the present invention and the comparative examples are shown in Table 1.
[0074] Table 1
[0075]
[0076] As can be seen from Table 1, the electrode material prepared by the preparation method of the present invention has high first efficiency and high cycle life; the first efficiency is above 85%, and the capacity retention rate after 50 cycles of charge and discharge is as high as above 90%.
[0077] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the technical solution. Those skilled in the art should understand that those modifications or equivalent substitutions of the technical solution of the present invention that do not depart from the purpose and scope of the technical solution should be included in the scope of the claims of the present invention.
Claims
1. A lithium-ion battery silicon-carbon negative electrode material, characterized in that: It is a double-layer core-shell structure, which consists of a silicon core, a buffer layer and a carbon layer from the inside to the outside. The mass fraction of each layer is: silicon core 40-60%, buffer layer 35-55%, carbon shell 5-10%; The lithium-ion battery silicon-carbon negative electrode material is prepared by the following method: S1, preparing silica aerogel coated silicon powder structure Si@SiO2; S2, subjecting the silica aerogel-coated silicon powder structure Si@SiO2 to high-temperature thermal reduction to obtain a porous silicon oxide compound-coated silicon powder structure Si@SiOx, wherein 0<x<2; S3, adding carbon material to the porous silicon oxide compound coated silicon powder structure Si@SiOx obtained in step S2 to coat the carbon material to obtain a silicon-carbon negative electrode material Si@SiOx@C; Wherein, the step S1 comprises: S11, dissolving methyl silicate and monomethyltrimethoxysilane in methanol, adding 0.15M hydrochloric acid, placing in a 40-60°C water bath with magnetic stirring, and hydrolyzing for 1-5 hours; adding methanol again to obtain silica sol; wherein the molar ratio of the methyl silicate, monomethyltrimethoxysilane, methanol, and hydrogen chloride is 1:0.1-2:5-15:0.01-1; the molar ratio of the methyl silicate to the methanol added again is 1:21-26; S12, adding silicon powder to the silicon dioxide sol obtained in step S11, and continuously stirring to obtain a sol in which the silicon powder is evenly dispersed; wherein the mass volume ratio of the silicon powder to the silicon dioxide sol is 24.5-56 g: 380-440 mL; S13, adding an alkaline alcohol solution to the sol in which silicon powder is uniformly dispersed obtained in step S12, controlling the gelation time to be 1 to 10 minutes, and obtaining a wet gel, and then placing it in a supercritical carbon dioxide environment for displacement drying for 1 to 20 hours; grinding and sieving the dried material to obtain a silicon dioxide aerogel-coated silicon powder structure Si@SiO2; The step S2 comprises: placing the silicon dioxide aerogel-coated silicon powder structure Si@SiO2 obtained in step S1 in a hydrogen-argon mixed atmosphere at 1100-1400°C for high temperature treatment for 1-5 hours to obtain a porous silicon oxide compound-coated silicon powder structure Si@SiOx (0<x<2); wherein the volume fraction of hydrogen in the mixed gas is 5%-20%; The step S3 comprises: S31, the porous silicon-oxygen compound-coated silicon powder structure Si@SiOx (0<x<2) obtained in S2 and the carbon source are mixed in a solution with a mass ratio of 1:1 of ethanol and water at a mass ratio of 1:1, and ultrasonicated for 30-100 minutes; S32, placing the mixed solution after ultrasonic treatment in a hydrothermal reactor, and hydrothermally treating it in an environment of 100-300° C. for 1-10 h; S33, after being completely dried in a blast oven, carbonize at 300-600°C for 30-360 min to obtain the silicon-carbon negative electrode material Si@SiOx@C.
2. The lithium-ion battery silicon-carbon negative electrode material according to claim 1, characterized in that: The buffer layer is a porous silicon-oxygen compound SiOx, wherein 0<x<2.
3. The lithium-ion battery silicon-carbon negative electrode material according to claim 1, characterized in that: The silicon powder particle size is 200-1000 nm.
4. An application method of a lithium-ion battery silicon-carbon negative electrode material, characterized in that: The silicon-carbon negative electrode material according to any one of claims 1 to 3 is used to prepare the negative electrode plate.
5. The application method of the lithium ion battery silicon-carbon negative electrode material according to claim 4, characterized in that: The preparation method of the electrode negative electrode sheet is as follows: according to the mass percentage, 60-80% of the silicon-carbon negative electrode material and 2-25% of the conductive agent are fully ground, and then 5-20% of the binder is added, and the mixture is fully mixed, and then coated on the copper foil with a thickness of 200 μm, and air-dried until the surface is completely solidified, and then compacted and dried in a vacuum environment at 120° C. for 5-20 hours to obtain the electrode negative electrode sheet.
6. The application method of the lithium ion battery silicon-carbon negative electrode material according to claim 5, characterized in that: Calculated by mass percentage, the silicon-carbon negative electrode material is 70%, the conductive agent is 20%, and the binder is 10%, or the silicon-carbon negative electrode material is 80%, the conductive agent is 10%, and the binder is 10%.
Citation Information
Patent Citations
Titanium-silicon-carbon anode material with core-shell garnet structure and its preparation method
CN109713242B
Lithium battery porous silicon-oxygen-carbon negative electrode material capable of inhibiting volume expansion and preparation method thereof
CN112421018A